Strain Hardening in an AZ31 Alloy Submitted to Rotary Swaging - Trojanová, Zuzanka; Drozd, Zdeněk; Halmešová, Kristýna; Džugan, Ján; Škraban, Tomáš; Minárik, Peter; Németh, Gergely; Lukáč, Pavel (Materials (Basel, Switzerland), 2020)
An extruded magnesium AZ31 magnesium alloy was processed by rotary swaging (RSW) and then deformed by tension and compression at room temperature. The work-hardening behaviour of 1-5 times swaged samples was analysed using Kocks-Mecking plots. Accumulation of dislocations on dislocation obstacles and twin boundaries is the deciding factor for the strain hardening. Profuse twinning in compression seems to be the reason for the higher hardening observed during compression. The main softening mechanism is apparently the cross-slip between the pyramidal planes of the second and first order. A massive twinning observed at the deformation beginning influences the Hall-Petch parameters.
Keywords: dislocation density; residual stresses; magnesium alloy AZ31; grain size; strain hardening; twinning